2012
DOI: 10.1002/hrm.21463
|View full text |Cite
|
Sign up to set email alerts
|

Building ambidexterity: The role of human resource practices in the performance of firms from Spain

Abstract: Both researchers and managers are increasingly interested in how firms can pursue ambidextrous learning—that is, simultaneously exploring new knowledge domains while exploiting current ones. In this study, we attempt to bring human resource management into this forum by introducing and testing how high‐involvement human resource practices shape the social climate that affects the firm's ambidextrous learning and subsequent performance. A field study of 198 companies from Spain showed that high‐involvement huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
215
1
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(231 citation statements)
references
References 61 publications
12
215
1
3
Order By: Relevance
“…Using the context of the emerging economies and cross-border M&As involving 84 deals, we found that formalized HR practices have a positive effect in enhancing the organizational ambidexterity of EMNEacquired subsidiaries. These findings support those of recent studies indicating that HR systems that assume the form of a high-performance work system can be an important antecedent of ambidexterity (Prieto andPilar Pérez Santana, 2012, Patel et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Using the context of the emerging economies and cross-border M&As involving 84 deals, we found that formalized HR practices have a positive effect in enhancing the organizational ambidexterity of EMNEacquired subsidiaries. These findings support those of recent studies indicating that HR systems that assume the form of a high-performance work system can be an important antecedent of ambidexterity (Prieto andPilar Pérez Santana, 2012, Patel et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…It has been suggested that organizational ambidexterity plays an important role in enhancing the performance of firms Birkinshaw, 2008, Raisch et al, 2009), but its potentially enabling antecedents are not well known, and existing studies often report conflicting results (Raisch and Birkinshaw, 2008). Recently, scholars have focused their attention on understanding the role of HR management practices on organizational ambidexterity (Prieto andPilar Pérez Santana, 2012, Patel et al, 2013), while others have focused on top management team characteristics and their influence on organizational ambidexterity (Simsek, 2009). To date, both streams of literature (HR and leadership) have evolved separately, with little cross-fertilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Prieto and Santana (2012) identified that the commitment and involvement of human resources in organizations is positively related to social climate, which in turn facilitates the development of ambidexterity and improves performance. Ramachandran (2012) argues that ambidexterity can be acquired not only through the balance between exploration and exploitation actions, as called for March (1991), but also through actions directed at one of the dimensions in particular.…”
Section: Ambidexteritymentioning
confidence: 99%
“…Considering employees as a key source of competitive advantage, strategic human resource management is gaining increasing importance in knowledge-based economies and rapidly changing environments (Prieto and Santana 2012;Sun et al 2007). As valuable, rare and inimitable assets for organizations because of their firm-specific, socially complex and path-dependent characteristics, human resource practices help firms obtain sustainable competitive advantages (Collins and Clark 2003).…”
Section: Introductionmentioning
confidence: 99%